2021
DOI: 10.1016/j.jtcme.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like and antidepressant-like effects of ethanol extract of Terminalia chebula in mice

Abstract: Terminalia chebula (T.chebula) fruit is referred as “King of Medicines” in Tibet and is listed as a key plant in “Ayurvedic Materia Medica” due to its diverse pharmacological activity. The present study was aimed to investigate the comorbid antidepressant-like and anxiolytic-like effects of ethanol extract from T.chebula fruit using experimental behavioral tests in mice. In addition, the study explored the effects of extract on monoamine oxidase –A (MAO-A) levels in mouse brain. Two doses of the T.chebula extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The acute toxicities were carried out following the Organization for Economic Cooperation and Development's recommendations (OECD 423) ( Mani et al, 2021 ). Three female rats of similar weight and age were allocated for each step.…”
Section: Methodsmentioning
confidence: 99%
“…The acute toxicities were carried out following the Organization for Economic Cooperation and Development's recommendations (OECD 423) ( Mani et al, 2021 ). Three female rats of similar weight and age were allocated for each step.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the anxiolytic activity of the same extract treatment was evidenced by a significant increase in the duration of time spent in the open arm and the number of head dips in the elevated plus-maze model. The results showed that T. chebula fruits could be an alternative for treating numerous central nervous system disorders such as antidepressants and anxiety [ 148 ]. CA, found in the extracts of T. chebula, exhibited p < 0.01 (in FST) and p < 0.05 (in TST) independent of dose when investigated for antidepressant activity.…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…Anxiety is a severe psychological situation associated with negative emotional experiences (Mani et al 2021). This disorder is one of the most common community illnesses affecting about 2-6% of the world population (Mani et al 2021).…”
Section: Anxiolytic Activitiesmentioning
confidence: 99%
“…Anxiety is a severe psychological situation associated with negative emotional experiences (Mani et al 2021). This disorder is one of the most common community illnesses affecting about 2-6% of the world population (Mani et al 2021). Previous studies reported the anxiolytic actions of medicinal plants (Doukkali et al 2015;Elakhal et al 2021;Lobina et al 2018).…”
Section: Anxiolytic Activitiesmentioning
confidence: 99%